FLEXURAL BEHAVIOR OF BAMBOO REINFORCED FERROCEMENT PANELS - Mukta S. Bangar; Dr. U. R. Kawade (International Journal of Innovations in Engineering Research and Technology, 2024)
Ferrocement is an emerging technology that differs from conventional reinforced concrete by the manner in which the reinforcing elements are dispersed and arranged. It consist of closely spaced, multiple layers of wire mesh embedded in cement mortar. Traditionally steel is used as reinforcement in concrete structures; but because of cost and availability, replacement of steel with some other suitable material as reinforcement is now a major concern. The construction industry is the main consumer of energy and materials in most of the countries. Since Bamboo is a natural, ecologically friendly, cheap and also readily available material; it can be use as a substitute of wire meshes in reinforcing of Ferrocement structures. This study describes the results of testing of Ferrocement beams reinforced with different number of Bamboo mesh layers and variation in spacing of bamboo reinforcement. The main objective of these experimental tests is to study the effect of using different numbers of Bamboo mesh layers and spacing variation on the Flexural strength of Ferrocement beams.